Chronic subdural haematoma management: an iatrogenic complication. Case report and literature review - Vladislav, Pavlov (BMJ Publishing Group, 2012)
The authors report the case of a 45-year-old woman who presented to our institution with 10 days history of confusion and signs of progressive raised intracranial pressure as a result of a minor head injury occurred 4 weeks before. A brain CT-scan showed a large right hemispheric chronic subdural haematoma which was, as routinely, treated by burr-hole craniostomy and closed-drainage. Although the procedure was uneventful, the next day the patient developed a mild left hemiparesis associated to a slight global status worsening. A brain CT scan showed an intracerebral position of the drain with diffuse brain oedema and midline shift. Following drain removal the patient developed a serious neurological deterioration dropping the Glasgow coma scale to 8/15 as the result of an intracerebral and intraventricular haemorrhage along the removed drain trajectory. The clinical features of this iatrogenic complication are reported analysing also globally chronic subdural haematoma management and discussing pertinent literature.